The Study of Figurative Terracottas: A Cautionary Tale from a Personal Perspective - Jaimee P. Uhlenbrock (Les Carnets de l’ACoSt)
In the study of Greek figurative terracottas there are many pitfalls that have resulted from out-dated notions that continue to influence coroplastic scholarship. The young researcher, in particular, must be attentive to the sources of an argument and employ critical judgement in order to avoid misdirection when interpreting coroplastic material.